Alteration of cell aggregation and adhesion in Dictyostelium amoeba by an overexpression of paracaspase protein - J. Saheb, Entsar (Iraqi Journal of Science, 2023)
Dictyostelium discoideum amoeba is a powerful system to study gene function through genetic and functional analysis. Paracaspase (Pcp) is a caspase-like protein that has recently identified in D. discoideum. Study paracaspase molecular function in Dictyostelium will provide insight into its cellular role in more complex organisms and the possibility to use it as a drug target against the parasitic amoeba. In this study, pcp was tagged with Green Fluorescent Protein (GFP) and over-expressed in the cell. The knockout version of pcp (pcp-) was also investigated. In the course of our examination, it was observed that cells overexpress Pcp was unable to complete the developmental process, leading us to examine its role in development. Those cells were unable to initiate early development and failed to aggregate under starvation conditions. Aggregation is severely defected as cells have decreased cell-cell cohesion. In particular, these cells demonstrated a reduction in adhesion. This data suggests that over-expression of Pcp causes a signaling defects crucial to normal development in Dictyostelium. On the other hand, cells with pcp- mutant demonstrated larger aggregation in normal media as well as under starvation conditions compared to the control cell lines. As a result, we propose that Dictyostelium Pcp is a regulated protein involved in cellular functions including signal relay pathways that are essential for cell aggregation and development. Thus, Pcp protein is a candidate drug target against the amoebic parasitic infection by prevent development to their infective stages.